S&T Cooperation Foresight Europe – Southeast Asia - Florian Gruber; Alexander Degelsegger (Foresight and STI Governance, 2010)
Thе paper provides the first results of multi-stage foresight process aimed at evaluating prospects of S&T cooperation between EU and Southeast Asian countries. It describes the procedure and the results of a scenario building workshop held in Bogor, Indonesia, where drivers and shapers of co-operation between mentioned regions for 10-years perspective were derived. In addition, the distinctive features of applying foresight methodology to the issue of multilateral S&T cooperation are analysed.